PEMANFAATAN GAME BASED LEARNING DAN AI DALAM ASESMEN PEMBELAJARAN PAI: TINJAUAN LITERATUR - Rofiatus Sa'adah; Abdul Munip (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study is based on the need for more interactive and adaptive assessment in Islamic Religious Education (PAI), as conventional assessment still tends to focus on written and oral tests that mainly measure cognitive achievement. This study aims to analyze the use of Game-Based Learning (GBL) integrated with Artificial Intelligence (AI) in PAI assessment. The method used is a literature review by examining relevant books, journal articles, proceedings, and scientific studies related to GBL, AI, digital assessment, and PAI learning. The findings show that GBL can increase students’ motivation, participation, and engagement through game elements such as quizzes, scores, challenges, rewards, and direct feedback. AI supports this process through automatic feedback, adaptive question difficulty, and real-time learning data analysis. The integration of GBL and AI also allows assessment to move beyond cognitive measurement toward a more holistic evaluation that includes affective aspects, skills, learning involvement, and character development. However, its implementation still faces challenges, including limited technological infrastructure, unequal digital literacy, and the limited use of adaptive AI features in learning platforms. This study concludes that GBL and AI can be used as innovative approaches to PAI assessment when supported by proper pedagogical design, teacher readiness, and adequate digital infrastructure.